Relative adrenal insufficiency in chronic liver disease: its prevalence and effects on long‐term mortality. Issue 7 (30th July 2014) - Jang, J. Y.; Kim, T. Y.; Sohn, J. H.; Lee, T. H.; Jeong, S. W.; Park, E. J.; Lee, S. H.; Kim, S. G.; Kim, Y. S.; Kim, H. S.; Kim, B. S.
Summary Background The relationship between relative adrenal insufficiency (RAI) and chronic liver disease is unclear. Aim To determine the frequency with which RAI is observed in noncritically ill patients at various stages of chronic liver disease, and the correlation between RAI and disease severity and long‐term mortality. Methods In total, 71 non‐critically ill patients with liver cirrhosis (n = 54) and chronic hepatitis (n = 17) were evaluated prospectively. A short stimulation test (SST) with 250 μg of corticotrophin was performed to detect RAI. RAI was defined as an increase in serum cortisol of <9 μg/dL in patients with a basal total cortisol of <35 μg/dL. Results RAI was observed in only 13 (24.1%) of 54 patients with cirrhosis. Compared to those without RAI, cirrhotic patients with RAI had significantly higher Child‐Turcotte‐Pugh score (10.3 ± 1.7 vs. 7.1 ± 1.8, mean ± s.d., P < 0.001) and Model for End‐Stage Liver Disease score (14.5 ± 6.6 vs. 9.4 ± 3.7, P = 0.017). The cortisol response to corticotropin was negatively correlated with the severity of cirrhosis (P < 0.05). In addition, the mortality rate was higher in cirrhotic patients with RAI (69.2%) than in those without RAI (4.9%; P < 0.001) during the follow‐up period of 20.1 ± 13.5 months (range, 5.8–51.1 months). The cumulative 1‐year survival rates in cirrhotic patients with and without RAI were 69.2% and 95.0%, respectively (P = 0.05), while the corresponding cumulative 3‐year survival rates were 0% and 95.0% (P < 0.001). Conclusions Relative adrenal insufficiency is more commonly observed in those with severe cirrhosis, and is clearly associated with more advanced liver disease and a shortened long‐term survival. This suggests that relative adrenal insufficiency is an independent prognostic factor in non‐critically ill patients with cirrhosis.